Gut Flora in Autistic Children as Biomarker for Autism in Thi-Qar Province/Iraq - Faten Naeem Abbas; Fadhil Abbas Munshed; Awatif Hamed Issa (University of Thi-Qar Journal of Science, 2020)
This is the first study that investigated the microbial factor as biomarker in autistic children and discuss roles of this factor in the pathogenesis of autism. The participants in current study were 145 persons, only 50 sample of stool  could collected (35 autistic children and 15 healthy children). Autistic children were attended to autism unit at Disabled Hospital in Thi-Qar province, Iraq during the period from January to November 2016.        The results showed males (81%) more than female (19%) with ratio 4:1 and also results explain the age group of 3-5 years recorded the highest percentage (41.05%). Distribution of autistic children according to sibling showed six were brotherly with occurrence rate 6.3%. Stool samples were subjected to examination and culture.The total aerobic count of isolated bacteria was 140 isolates.  Gram-negative isolates were identified by API Enterobacteriaceae system. The results were Escherichia coli, Enterobacter cloacae, Klebsiella pneumonia, Pseudomonas aeruginosa and Proteus mirabilis with percentage 38.5%, 19.23%, 11.53%,7.69%,  and 3.84% respectively.  On the other hand, gram positive cocci isolates included Enterococcus faecalis, Staphylococcus aureus and Staph. epidermidis with percentage 11.53%, 4.80% and 2.88% respectively. A significant difference (P≤0.05) was recorded between bacterial isolates.        Quantity and quality of isolated bacteria (colony/g *104) were done.  E.coli isolates were the highest count with 261*104 colony/g while, Staphylococci epidermidis were recorded the worse colony count with 30*104 colony/g. The quality results showed Escherichia coli the most common gram negative bacterial isolates (38.46%). On the other hand, the highest gram positive cocci isolates were included Enterococcus faecalis (11.53%), with significant difference (P≤0.05) between bacterial isolates.       The ability of bacterial isolates to produce histidine decarboxylase was examined on Niven medium. The positive result  include colonies with purple halo around them. Only 10 isolates (25%) from all isolates were produce histidine belong to E.coli. On other hand, result of parasite examination explain no parasite in all samples.           From this study can conclusion the altered gut microflora may play an essential role in the pathogenesis of autism. Despite  the  accurate evidence,  this  etiological  heterogeneity is still not recognized by autism researchers, and most studies fail to take it into account.